Sequence-Specific Detection of Aristolochia DNA – A Simple Test for Contamination of Herbal Products - Sgamma, Tiziana; Masiero, Eva; Mali, Purvi; Mahat, Maslinda; Slater, Adrian (Frontiers in Plant Science, 2018)
Herbal medicines are used globally for their health benefits as an alternative therapy method to modern medicines. The market for herbal products has increased rapidly over the last few decades, but this has in turn increased the opportunities for malpractices such as contamination or substitution of products with alternative plant species. In the 1990s, a series of severe renal disease cases were reported in Belgium associated with weight loss treatment, in which the active species Stephania tetrandra was found to be substituted with Aristolochia fangchi. A. fangchi contains toxic aristolochic acids, which have been linked to kidney failure, as well as cancers of the urinary tract. Because of these known toxicities, herbal medicines containing these compounds have been banned in some countries, but they are still available via the internet and in alternate formulations. The substitution seems to have occurred due to use of the same Chinese Pin Yin name (Fang Ji) to describe the roots of A. fangchi, S. tetrandra and Cocculus species. As a result, plant genera such as Stephania, Sinomenium and Cocculus were also blacklisted due to their potential to be contaminated with Aristolochia, despite the fact that they may offer numerous health benefits. Plants of different species can be distinguished using morphological, chemical or DNA based methods. With the purpose of resuming the trade of these herbs, several chemical analysis methods have been used to identify and differentiate Aristolochia species. However, such methods are expensive and depend on multiple physiological factors. In contrast, DNA barcoding is a fast, accurate technique that can identify species using sequences from a short, standardised region of DNA and is suitable for high-throughput analysis of samples at an industrial scale. In this study, a DNA based method based on Quantitative Real-Time PCR was tested to detect and distinguish Aristolochia species from a range of medicinal plants that could potentially be contaminated with Aristolochia material. Specific primers were designed to confirm that Aristolochia can be detected, even in small amounts, if it is present in the products, fulfilling the aim of offering a simple, cheaper and faster solution than the chemical methods.